Literasi Halal Sebagai Salah Satu Upaya Pengembangan UMKM Di Kabupaten Malang - Sulastri Sulastri; Umi Nuraini; Ferby Mutia Edwy (Karunia: Jurnal Hasil Pengabdian Masyarakat Indonesia, 2023)
The number of MSMEs that have halal certificates is still far less than large industries, including MSMEs in Kedungsalam Village, Donomulyo District, Malang Regency. Based on these problems, the Accounting Department of Universitas Negeri Malang (UM) held a halal literacy activity for MSMEs. This halal literacy activity has never been obtained by participants before. The purpose of this activity is that in the future MSMEs in Kedungsalam Village can improve product quality through halal certification, so that they can survive and compete in the globalization era. This service activity is considered right on target, because MSME products that are not yet halal certified can register through the Halal Center at UM. The UM Halal Center has been officially established since early 2019 which has a role in providing services to the community's needs for halal certification, namely accompanying, fostering, and overseeing halal product guarantees.